A new species of Longitarsus (Coleoptera: Chrysomelidae) feeding on Chinese potato, Plectranthus rotundifolius (Lamiaceae) in southern India - Prathapan, K. D.; Faizal, M. H.; Anith, K. N. (Zootaxa, 2005)
Longitarsus serrulatus, a new species feeding on Plectranthus rotundifolius (Lamiaceae) in Kerala, India, is described and illustrated. Host plant data and ecological information are provided.